2023
DOI: 10.3390/axioms12030248
|View full text |Cite
|
Sign up to set email alerts
|

The VM2D Open Source Code for Two-Dimensional Incompressible Flow Simulation by Using Fully Lagrangian Vortex Particle Methods

Abstract: This article describes the open-source C++ code VM2D for the simulation of two-dimensional viscous incompressible flows and solving fluid-structure interaction problems. The code is based on the Viscous Vortex Domains (VVD) method developed by Prof. G. Ya. Dynnikova, where the viscosity influence is taken into account by introducing the diffusive velocity. The original VVD method was supplemented by the author’s algorithms for boundary condition satisfaction, which made it possible to increase the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The structure and options of the VM2D code are briefly described in [9]. However, the development of the VM2D continues, some other features are available in recent versions, as well as improved algorithms for essential operations.…”
Section: The Vm2d Code and Results Of Simulation In Model Problemsmentioning
confidence: 99%
“…The structure and options of the VM2D code are briefly described in [9]. However, the development of the VM2D continues, some other features are available in recent versions, as well as improved algorithms for essential operations.…”
Section: The Vm2d Code and Results Of Simulation In Model Problemsmentioning
confidence: 99%
“…Marshal (США) и другими. Коллективом авторов [20,21] разработан пакет VM2D, свободно доступный по ссылке https://github.com/vortexmethods/VM2D с исходным кодом на языке C++. Он предназначен для решения широкого круга плоских задач, в том числе в сопряженной гидроупругой постановке.…”
Section: программные реализации вихревых методовunclassified
“…At the same time, the results of the accuracy investigation of known numerical schemes (that can be applied in 2D problems being solved by vortex particle methods) performed for model problems with known exact solution [5], show that the error can be high enough, and it can be the most significant factor that bounds the accuracy of the flow simulation. A more detailed review of the problems being solved, as well as the VM2D code developed directly by the authors which allows simulating twodimensional incompressible flows around movable and immovable airfoils, is presented in [6]. In the present paper, the original approach is suggested that allows for improving the accuracy of the BIE solution for airfoils with sharp edges or corner points where the exact solution has the singularity.…”
Section: Introductionmentioning
confidence: 99%